Knowledge, Attitudes, Practices, and the Factors that Influence Breastfeeding among Mothers attending a Primary Health Center in Sulaimani City (Indian Journal of Forensic Medicine & Toxicology, 2020)
This study was performed to assess knowledge, attitudes, and practices towards breastfeeding and identifyfactors impacting this practice among mothers. A descriptive case-series study was carried out among 220mothers who had a child less than 2 years, in Ibrahim Pasha Health Center in Sulaimani city, between the9th of August 2018 and 20th of November 2018. The convenience sampling method was used to select thesubjects. Mean age of the mothers was 29.37 years. More than half (56.8%) of the mothers were encouraged forbreastfeeding, the main encouragement factors were husbands, medical staff, and other families (45%, 22%,and 15% respectively). More than one third (37.7%) of the mothers ceased breastfeeding, the main motiveswere producing insufficient milk, child refusal and child’s disease (31%, 25%, and 17% respectively). Theassociation between mode of delivery and types of feeding was statistically significant (P=0.028); exclusivebreastfeeding was high in the normal delivery group. Overall, the mothers had a good knowledge and apositive attitude toward breastfeeding. Only 30.5% of the mothers started breastfeeding within the first hourafter labour. An extreme number (95%) of the mothers fed colostrum to their baby. Merely 30.5% of theparticipants fed their babies exclusively.